THE REPRESENTATION OF CHINESE AND MULTICULTURALISM IN BUKALAPAK’S BU LINDA ADVERTISEMENT - Bramantya, Akbar Aria; Suhendi, Indrawan Dwisetya (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
Indonesia is a multi-ethnic country that is rich in cultural diversity. However, certain ethnic identities, such as Chinese, are often marginalised in their socio-political history. Bu Linda's advertisement from Bukalapak, released to celebrate Chinese New Year, attempts to counter racist sentiments and promote multiculturalism. This study employs qualitative analysis to explore how advertisement portrays the relationship among ethnicity, class, and authority within the context of Indonesian society. Hall's (1997) theory of representation is used to examine how racial and ethnic identities are portrayed in the advertisement, Bhabha's (1994) social articulation is used to analyze how the diversity of identities among the characters intertwines in the advertisement, and Pratista's (2008) cinematographic analysis is used to examine how the depiction of audio-visual communication in the advertisement shapes the understanding of the message. The findings show that Bu Linda's advertising video represents Indonesia's multicultural society through dynamic interactions and the merging of identities between Javanese (Ari), Ambonese (Mario), and Chinese (Bu Linda) as student boarders and the house owner, in a shared space depicted using a boarding house setting. Moreover, this advertisement serves as propaganda that aims to evoke public sympathy for Indonesian unity through the representation of social and cultural strength.